Correlation between ultrasonographic and histopathological findings of hysterectomy specimen in patients with abnormal uterine bleeding - Mahajan, Kaushik; Devi, R. K. Praneshwari; Singh, Ajitkumar; Lairenjam, Dipenty; Singh, Leimapokpam Roshan; ., Nungsangtemjen; Roy, Madhumita; Jeevana, C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: AUB is a common and debilitating condition and it is one of the main gynaecological reasons for hysterectomy. Ultrasonography can be as good as histopathology (HPE) in the diagnosis of abnormal uterine bleeding. Hence, our study was conducted to validate the ultrasonographic findings with HPE findings in diagnosis of AUB. Methods: A hospital based cross-sectional analytical study was conducted among 86 patients with abnormal uterine bleeding in the department of Obstetrics and Gynaecology in collaboration with department of Pathology, RIMS, Imphal from September 2017 to March 2019. The clinical history and socio demographic profile were collected using a pre-designed proforma. General physical examination, pelvic examination and ultrasonagraphy was carried out and the hysterectomy specimens were subjected to histopathological examination. Results: Fibromyoma was diagnosed by ultrasound in 62.8% of the patients and it was the common diagnosis in this study. The sensitivity, specificity, positive predictive value, negative predictive value and kappa statistics of USG for diagnosing leiomyoma was 92.9%, 93.3%, 96.3%, 87.5% and 84.9% respectively. The sensitivity, specificity, positive predictive value, negative predictive value and kappa statistics of USG for diagnosing adenomyosis was 53.8%, 98.6%, 87.5%, 92.3% and 62.3% respectively. Conclusions: The study provides an evidence that ultrasonography has good diagnostic accuracy as histopathology in the diagnosis of fibroid in patients with abnormal uterine bleeding. However, as with all the diagnostic procedures, the utility of ultrasound in the diagnosis of adenomyosis is questionable, since it has a low sensitivity amidst good specificity.